THE IMPLEMENTATION OF THE MONTESSORI APPROACH TO INTRODUCE MULTICULTURAL EDUCATION IN EARLY CHILDHOOD - Rina Jayani,; Sri Wulan, (PUPIL: International Journal of Teaching, Education and Learning, 2025)
This study aims to examine the importance of introducing multicultural education at an early age. This is based on the phenomenon observed in Indonesia, particularly in Jakarta, where many children are still unaware of the ethnic backgrounds and customs of each child's parents. Children with a multicultural understanding are expected to develop an attitude of tolerance. The Montessori approach, which includes cultural and scientific areas, helps teachers introduce cultural diversity and the uniqueness of various countries' cultures. This aims to instill respect for cultural uniqueness among children. The research methodology employs a qualitative approach, with data collected from teachers through Google Forms, in-depth interviews, and observations during class activity. The subjects of this study are teachers at Aluna Montessori School in South Jakarta. The results indicate that teachers believe multicultural education is important to introduce early but a lack of media and games designed to stimulate multicultural understanding in early childhood. Consequently, teachers create media and games based on their creativity. These findings can serve as a foundation for future research to develop educational games that introduce Indonesian culture in addition to international cultures.